The "Kansas City" sessions - Young, Lester 1909-1959 (GRP Records, 1997)
The great musician comes out for an overflow of classic performances
Jazz. - The 5th-6th works include vocals. - Compact discs. - Program notes by Loren Schoenberg (13 p. : ports.) inserted in container
Originally produced by Milt Gabler (#19-22) produced by John Hammond). Reissue produced by Orrin Keepnews
Enth.: Way down yonder in New Orleans #2 -- Way down yonder in New Orleans -- Countless blues -- Countless blues #2 -- Them there eyes #2 -- Them there eyes -- I want a little girl -- I want a little girl #2 -- Pagin' the devil -- Pagin' the devil #2 -- Three little words #2 -- Three little words -- Jo Jo -- I got rhythm #3 -- I got rhythm #2 -- I got rhythm -- Four o'clock drag -- Four o'clock drag #3 -- Laughing at life -- Good mornin' blues -- I know that you know -- Love me or leave me
Keywords: Jazz / 1931-1940; Jazz / 1941-1950; Jazz vocals; Saxophone music (Jazz); Clarinet music (Jazz)